2003
DOI: 10.1002/ffj.1235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic agriculture practices on the volatile aroma components of some essential oil plants growing in Egypt II: sweet Marjoram (Origanum marjorana L.) essential oil

Abstract: Sweet marjoram (German type) was grown in Egypt under the conditions of organic and traditional agriculture. Mature compost was used as an organic fertilizer, while ammonium sulphate was used as a chemical fertilizer. Two levels of each fertilizer were used during plant growth. The crops were harvested and hydrodistilled in June and September, the isolated essential oil was fractionated into oxygenated and hydrocarbon fractions, then each fraction was analysed by GC and GC-MS. The results showed that the fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 9 publications
5
26
0
Order By: Relevance
“…cisSabinene hydrat was found only in the supercritical extract in a low amount (1.1%). The composition of essential oil had a similar chemovariety to Central and Eastern European spices of marjoram (Baratta et al, 1998;Baser & Kirimer, 1993;Daferea et al, 2000;Edris et al, 2003;Lawrence, 1994;Novak et al, 2000;Novak et al, 2002;Pino et al, 1997;Vera & Chane, 1999). The ethanolic and supercritical extracts showed a similar composition, although in the SFE extract the content of terpinen-4-ol was almost twice as high as in the ethanolic extract.…”
Section: Qualitative Determination Of Essential Oil Components In Thementioning
confidence: 79%
See 1 more Smart Citation
“…cisSabinene hydrat was found only in the supercritical extract in a low amount (1.1%). The composition of essential oil had a similar chemovariety to Central and Eastern European spices of marjoram (Baratta et al, 1998;Baser & Kirimer, 1993;Daferea et al, 2000;Edris et al, 2003;Lawrence, 1994;Novak et al, 2000;Novak et al, 2002;Pino et al, 1997;Vera & Chane, 1999). The ethanolic and supercritical extracts showed a similar composition, although in the SFE extract the content of terpinen-4-ol was almost twice as high as in the ethanolic extract.…”
Section: Qualitative Determination Of Essential Oil Components In Thementioning
confidence: 79%
“…The essential oil obtained by steam distillation contains mainly terpinen-4-ol (>20%) which with (+)-cis-sabinene hydrate (3-18%) is responsible for the characteristic flavour and fragrance of marjoram oil. In addition to these compounds, a-and c-terpinene and terpinolene were the other major components (no-unless there is more than 20% present); thymol and carvacrol were determined in smaller amounts (Baratta et al, 1998;Baser & Kirimer, 1993;Daferea, Ziogas, & Polissiou, 2000;Edris, Shalaby, & Fadel, 2003;Ezzeddine, Abdelkefi, Ben Aissa, & Chaabouni, 2001;Lawrence, 1994;Novak et al, 2000;Novak, Langbehn, Pank, & Franz, 2002;Pino, Rosado, Estarron, & Fuentes, 1997;Vera & Chane, 1999). Antioxidant activity of marjoram essential oil (Baratta et al, 1998) and its purified substance (Jun et al, 2001) has been reported.…”
Section: Introductionmentioning
confidence: 97%
“…However, essential oils of thyme and rosemary were consistent with the pharmacopeial limits qualitatively rather than quantitatively. The chemical composition of the oils of cumin and marjoram showed qualitative and quantitative variability amongst essential oils from different geographical areas, variable agronomic and environmental factors [20][21][22]. It is documented that the chemical composition of essential oils is influenced by a variety of endogenous and exogenous factors.…”
Section: Resultsmentioning
confidence: 99%
“…The experiment allowed acting for 80 days, which the bed material converted into vermicompost and at end the vermicompost were collected. Diver (1998) reported that there are two main methods producing vermicompost tea: the method of fermentation (without aeration) and the method along with aeration. Through present experiment, vermicompost tea was produced by the method along with aeration.…”
Section: Production Of Vermicompost Vermiwash and Vermicompost Teamentioning
confidence: 99%